2018
DOI: 10.1136/jnnp-2017-316302
|View full text |Cite
|
Sign up to set email alerts
|

Functional lesional neurosurgery for tremor: a systematic review and meta-analysis

Abstract: Background: This work evaluates the consistency, effect size and incidence of persistent side effects of lesional

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 87 publications
0
17
0
2
Order By: Relevance
“…MRgFUS thalamotomy has emerged as an additional option for disabling ET. Because the first publication of favorable clinical results of MRgFUS thalamotomy in 2013, 5 a few additional reports have been provided regarding its results, 10,11 technical methods, 12 adverse effects, 13 and comparative outcomes with other therapeutic modalities 14 ; however, these studies have primarily been short term. 5,6,[9][10][11]15 With this treatment, the 12-month reduction rate of total CRST was 35% to 56%, hand tremor reduction rate was 40% to 78%, and disability reduction rate was 61% to 85% ( Table 2).…”
Section: Four-year Results Of Mrgfus Thalamotomymentioning
confidence: 99%
“…MRgFUS thalamotomy has emerged as an additional option for disabling ET. Because the first publication of favorable clinical results of MRgFUS thalamotomy in 2013, 5 a few additional reports have been provided regarding its results, 10,11 technical methods, 12 adverse effects, 13 and comparative outcomes with other therapeutic modalities 14 ; however, these studies have primarily been short term. 5,6,[9][10][11]15 With this treatment, the 12-month reduction rate of total CRST was 35% to 56%, hand tremor reduction rate was 40% to 78%, and disability reduction rate was 61% to 85% ( Table 2).…”
Section: Four-year Results Of Mrgfus Thalamotomymentioning
confidence: 99%
“…7 Later in its evolution, when drug-related complications become unmanageable, effective treatment can still be achieved with surgical interventions, 8 that is, deep brain stimulation (DBS) 9 and focal ablation by radiofrequency or gamma knife. [10][11][12] However, all existing therapeutic options remain symptomatic, and no therapy is currently available to stop or slow the process underlying the onset and progression of the neurodegeneration. Despite promising preclinical results, all previous attempts in this direction have failed.…”
mentioning
confidence: 99%
“…In the early stages of PD, motor features can be treated effectively with dopaminergic drugs, particularly levodopa . Later in its evolution, when drug‐related complications become unmanageable, effective treatment can still be achieved with surgical interventions, that is, deep brain stimulation (DBS) and focal ablation by radiofrequency or gamma knife . However, all existing therapeutic options remain symptomatic, and no therapy is currently available to stop or slow the process underlying the onset and progression of the neurodegeneration.…”
mentioning
confidence: 99%
“…However, studies on long-term effects as well as a direct comparison with RF lesioning are lacking. Since a recent systematic review reported the highest overall rate of persistent side effects after MRgFUS, compared to Gamma Knife radiosurgery and RF [17], in our opinion RF thalamotomy is still the preferred option.…”
Section: Lesioning Techniquesmentioning
confidence: 86%